'On-water' organic synthesis: a green, highly efficient, low cost and reusable catalyst system for biaryl synthesis under aerobic conditions at room temperature1. Issue 63 (10th July 2015) - Saikia, Bishwajit; Boruah, Preeti Rekha; Ali, Abdul Aziz; Sarma, Diganta
<x xml:space="preserve">Abstract</x> The PdCl2/sucrose/K2CO3/H2O system showed the superb catalytic activity towards the Suzuki reaction of a wide range of aryl/heteroaryl halides with diverse phenylboronic acids at room temperature with operational simplicity and shorter reaction time.